Analisis Nilai Laju Endap Darah pada Pasien Sindrom Koroner Akut dan Stable Angina di RSD dr. Soebandi Jember (The Erythrocyte Sedimentation Rate Analysis in Acute Coronary Syndrome and Stable Angina Patients at dr. Soebandi General Hospital) - Rizki Nur Fitria; Suryono Suryono; Rini Riyanti (UPT Percetakan dan Penerbitan Universitas Jember, 2017)
Erythrocyte sedimentation rate (ESR) is non-specific blood tests that can be used as a marker of chronic inflammation. Some proteins that affect the erythrocyte sedimentation rate are fibrinogen, lipoprotein, and immunoglobulins. These proteins elevate in patients with atherosclerosis and acute coronary syndrome. This study aimed to determine the relationship between erythrocyte sedimentation rate and the incidence of acute coronary syndrome and stable angina at dr. Soebandi General Hospital Jember. This analytic observasional study using cross-sectional design.This study used 40 samples, divided into four groups; stable angina, UA, NSTEMI, and STEMI. The average value of ESR were 12,1mm/h, 20,7mm/h, 28,9mm/h, and 25,3mm/h for stable angina, UA, NSTEMI, and STEMI, respectively. Kolmogorov-Smirnov statistical test showed significant difference between groups(p=0.001). It indicated that there was relationship between erythrocyte sedimentation rate and the incidence of acute coronary syndrome and stable angina in dr. Soebandi General Hospital Jember. Keywords: erythrocyte sedimentation rate, acute coronary syndrome, stable angina